2021
DOI: 10.1108/par-07-2020-0088
|View full text |Cite
|
Sign up to set email alerts
|

CFO attributes and accounting conservatism: evidence from Malaysia

Abstract: Purpose This paper aims to examine whether conditional conservatism is affected by chief financial officer (CFO) attributes as this issue is understudied in Malaysia. Given that CFOs have a direct responsibility for financial reporting, therefore, their individual attributes are important in influencing conservatism in financial reporting. Design/methodology/approach This study uses non-financial listed firms in the Main Market of Bursa Malaysia from the years 2016 until 2019. Findings The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 75 publications
3
8
0
4
Order By: Relevance
“…This is in comparison to 41 percent for Chinese CFOs (p=0.000), 62.5 percent for Indian CFOs (p=0.106) and 60 percent for CFOs from other ethnic groups (p=0.509). The positive impact of Malay executives, in this case CFOs, is consistent with the previous literature which found the presence/extent of Malay executives/directors led to greater voluntary disclosure (Haniffa & Cooke, 2002) and corporate social responsibility disclosure (Alazzani et al, 2019;Haniffa & Cooke, 2005), better accrual quality (Hashim, 2012), and more conservative approach in accounting (Ismail et al, 2021).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This is in comparison to 41 percent for Chinese CFOs (p=0.000), 62.5 percent for Indian CFOs (p=0.106) and 60 percent for CFOs from other ethnic groups (p=0.509). The positive impact of Malay executives, in this case CFOs, is consistent with the previous literature which found the presence/extent of Malay executives/directors led to greater voluntary disclosure (Haniffa & Cooke, 2002) and corporate social responsibility disclosure (Alazzani et al, 2019;Haniffa & Cooke, 2005), better accrual quality (Hashim, 2012), and more conservative approach in accounting (Ismail et al, 2021).…”
Section: Resultssupporting
confidence: 89%
“…denote no significant association.Apart from the studies listed in Table1, there are also empirical research in Malaysia linking CFO characteristics and earnings conservatism and quality of corporate reporting. Based on 1,004 firm-year observations,Ismail et al (2021) found the influence of CFO gender, age, education level, and ethnicity.…”
mentioning
confidence: 99%
“…Thus, they play an important role in providing FRQ (Aier et al , 2005; Ge et al , 2011). According to research conducted by Almeida and Lemes (2020), Collier and Wilson (1994), Ismail et al (2021), Yu (2021), the characteristics, such as educational background, play an important role in making decisions regarding financial policy. Hence, this study investigates the association between a CFO’s educational background and FRQ.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…An MBA degree is known to influence top managers' performance, as the upper echelons theory predicts that top managers' managerial backgrounds can better describe their strategic decisions and create consequences that affect organizational outcomes. Some researchers, such as Ismail et al (2021), find that CFOs with a master's degree report earnings more conservatively. Similarly, Sun et al (2021) documented that executives with MBA reporting earnings are less aggressive and conservative.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Of all senior managers, the chief financial officer (CFO) has the most impact on a firm’s financial reporting decisions (Zalata et al , 2021; Wang et al , 2021). Furthermore, regulators hold CFOs accountable for firms’ financial reports (Doan and Iskandar-Datta, 2020) as the CFO has an important responsibility for the fair presentation of the company’s financial statements and financial information (Ismail et al , 2021). However, despite the importance of CFOs in modern corporations (Xu et al , 2019), organisational researchers have largely ignored the central role of the CFO as a key decision maker (Vähämaa, 2017).…”
Section: Introductionmentioning
confidence: 99%